Dataset after seven years simulating hybrid energy systems with Homer Legacy (2020)
Homer Legacy software is a well-known software for simulation of small hybrid systems that can be used for both design and research. This dataset is a set of files generated by Homer Legacy bringing the simulation results of hybrid energy systems over the last seven years, as a consequence of the research work led by Dr. Alexandre Beluco, Federal University of Rio Grande do Sul, in southern Brazil. The data correspond to twelve papers published in the last seven years. Two of them describe hydro PV hybrid systems with photovoltaic panels operating on the water surface of reservoirs. One of these twelve papers suggests the modeling of hydropower plants with reservoirs and the other the modeling of pumped hydro storage, and a third still uses these models in a place that could receive both the two types of hydroelectric power plant. The other simulated hybrid systems include wind turbines, diesel generators, batteries, among other components. This data article describes the files that integrate this dataset and the papers that have been published presenting the hybrid systems under study and discussing the results. The files that make up this dataset are available on Mendeley Data repository at https://doi.org/10.17632/ybxsttf2by.2.